Bullous Mastocytosis Mimicking Congenital Epidermolysis Bullosa - Julio Cesar Salas-Alanis; Cesar Eduardo Rosales-Mendoza; Jorge Ocampo-Candiani (Karger Publishers, 2014)
A 2-month-old female infant was referred to DebRA Mexico from the Regional Children's Hospital because of a generalized dermatosis from birth characterized by multiple blisters and erosions on the trunk, face and limbs, associated with minor trauma. A skin biopsy showing subepidermal blisters associated with a dermal infiltrate of Giemsa-positive cells and CD117-positive antibody was consistent with the diagnosis of bullous mastocytosis. Treatment with oral antihistamines, topical steroids, and antibiotics was initiated, leading to a remission of the lesions.